Synthesis of Nanostructured Lipid Carriers Loaded Chitosan/Carbopol Hybrid Nanocomposite Gel for Oral Delivery of Artemether and Curcumin - Kumar, Arun; Behl, Tapan; Uniyal, Toshi; Chadha, Swati (Pharmaceutical Nanotechnology, 2020)
Background: Antimalarial therapy remains the utmost effective means for the management of malarial parasites in the liver and red blood cells. The application of these therapeutic agents is hampered by their improper application, hepato-toxicity caused by their continuous use, and degradation by hepatic enzymes. Methods: Recent advancements in drug delivery applications have shown potential in improving the pharmacological properties of artemether. Nanostructured lipid carriers (NLCs) loaded chitosan (CH)/Carbopol (CB) hybrid gel was prepared using glycerol monostearate (GMS) as solid lipid and clove oil as a liquid lipid for artemether (ART) and curcumin (CR) for its localized effect on the liver. Results: The smaller particle size ( 118 ± 1.0 nm) and high zeta potential (- 41.1 ± 6.46 mV) confirm the formulation and stability of NLCs. On the other hand, the shape and morphology of prepared NLCs and gel showed a spherical and wrinkled surface with a size range of 150-250 nm. The release studies of the NLC’s showed a controlled release of artemether ( 92%) and curcumin ( 83%) for up to 30 h. Photostability data showed that, approximately, 86.5 ± 0.3% and 60 ± 0.9% of nanoencapsulated artemether and curcumin were still detected on exposure to sunlight, respectively. It has been found from the permeation study that 69.8% and 49.1% of the drug was permeated across the mucus membrane in 24 h with a significant increase (P < 0.05) in flux as well as permeability coefficients. Conclusion: The overall results showed that prepared CH/CB/NLCs hybrid gel could be a promising vehicle for the effective delivery of ART and CR for the management of malarial parasites. Lay Summary: Antimalarial therapy remains the utmost effective means for the management of malarial parasites in liver and red blood cells. Recent advancements in drug delivery applications have shown potential in improving the pharmacological properties of artemether. Application of these therapeutic agents hampered by their improper application, hepato-toxicity caused by their continuous use and degradation by hepatic enzymes. To manage the above issues, we synthesize nanostructured lipid carriers (NLC’s) loaded chitosan (CH)/Carbopol (CB) hybrid gel using glycerol monostearate (GMS) as solid lipid and clove oil as liquid lipid for artemether (ATR) and curcumin (CR) for its local action in liver and the major criteria were to find a protective barrier with hepatoprotective nature of the curcumin.
Keywords: hepato-toxicity